Safe Harbor Agreement: A Regulatory Assurance under the Endangered Species Act - Melissa M. Kreye; Elizabeth F. Pienaar; Raoul K. Boughton; Lindsey Wiggins (EDIS)
The involvement of the private sector is critical for the conservation and recovery of many species, but landowners’ fears that increased management restrictions could keep them from enjoying their land can present a challenge to securing their trust and assistance in conservation efforts. A Safe Harbor Agreement is a regulatory assurance that removes the risk of additional regulation in the future and encourages landowners to maintain important habitat on their lands. This 3-page publication provides Extension agents, decision-makers, and landowners with a basic understanding of a landowner’s obligations and the benefits of enrolling. Written by Melissa M. Kreye, Elizabeth F. Pienaar, Raoul K. Boughton, and Lindsey Wiggins, and published by the Wildlife Ecology and Conservation Department, December 2015.